2014
DOI: 10.1088/2041-8205/796/2/l22
|View full text |Cite
|
Sign up to set email alerts
|

Water Trapping on Tidally Locked Terrestrial Planets Requires Special Conditions

Abstract: Surface liquid water is essential for standard planetary habitability. Calculations of atmospheric circulation on tidally locked planets around M stars suggest that this peculiar orbital configuration lends itself to the trapping of large amounts of water in kilometers-thick ice on the night side, potentially removing all liquid water from the day side where photosynthesis is possible. We study this problem using a global climate model including coupled atmosphere, ocean, land, and sea-ice components as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 33 publications
(35 reference statements)
3
62
0
1
Order By: Relevance
“…Godolt et al (2015) shows that taking oceanic circulation into account produces surface habitable conditions for planets orbiting F-type stars instead of a snowball state. Our results would likely be different if we had considered other types of planets such as an Earth-like planet, a land planet, a planet with a Pangea-like continent, or a planet with archipelagos (e.g., Yang et al 2014). …”
Section: Discussionmentioning
confidence: 70%
“…Godolt et al (2015) shows that taking oceanic circulation into account produces surface habitable conditions for planets orbiting F-type stars instead of a snowball state. Our results would likely be different if we had considered other types of planets such as an Earth-like planet, a land planet, a planet with a Pangea-like continent, or a planet with archipelagos (e.g., Yang et al 2014). …”
Section: Discussionmentioning
confidence: 70%
“…This is despite the much lower relative number density of the suprathermal populations (∌5% at 1 AU) as compared to the thermal core [Feldman et al, 1975]. Recent investigations have shown that the heat flux is closely related to the relative drift between the core and the halo populations [Bale et al, 2013], which may be the relic of an electron two stream instability that develops in the low corona [Che and Goldstein, 2014]. It has also been shown that when a clear strahl beam is observed, the majority of solar wind heat flux is carried by the strahl electrons [Pilipp et al, 1987a].…”
Section: Introductionmentioning
confidence: 95%
“…Let us assume that the planet starts with a global ocean, possibly covered by sea-ice wherever cold enough. This experiment has been done by Yang et al (2014) 5 with a 325 m-deep ocean. They showed that in such a configuration, winds carry sea-ice toward hot regions and the ocean carries heat toward cold ones, so that an equilibrium can be found with less than 10 m of sea-ice in the coldest regions 6 .…”
Section: Transition From Small To Large Water Inventorymentioning
confidence: 99%